The sense of adharma - Glucklich, Ariel (Oxford University Press, 1994)
Addressing one of the most difficult conceptual topics in the study of classical Hinduism, Ariel Glucklich presents a rigorous phenomenology of dharma, or order. The work moves away from the usual emphasis on symbols and theoretical formulations of dharma as a religious and moral norm. Instead, it focuses on images that emerge from the basic experiential interaction of the body in its spatial and temporal contexts, such as the sensation of water on the skin during the morning purification, or the physical manipulation of the bride during the marriage ritual. Images of dharma are examined in myths, rituals, art, and even the physical landscape of the Hindu world. The varied and contingent experiences of dharma infuse it with a meaning that transcends a false analytical distinction from adharma, or chaos. Glucklich shows that when dharma is experienced by means of living images, it becomes inescapably temporal, and therefore inseparable from adharma.